2016
DOI: 10.1016/j.cell.2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Fanconi Anemia Proteins Function in Mitophagy and Immunity

Abstract: Fanconi anemia (FA) pathway genes are important tumor suppressors whose best-characterized function is repair of damaged nuclear DNA. Herein, we describe an essential role for FA genes in two forms of selective autophagy. Genetic deletion of Fancc blocks the autophagic clearance of viruses (virophagy) and increases susceptibility to lethal viral encephalitis. FANCC interacts with Parkin; is required in vitro and in vivo for clearance of damaged mitochondria; and decreases mitochondrial ROS production and infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
218
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(230 citation statements)
references
References 52 publications
10
218
0
2
Order By: Relevance
“…17,28,29 In DBA, hyper-activation of mTOR is congruent with the increment in OXPHOS over glycolytic metabolism, while in FA and SDS, hyper-activation of mTOR might suggest the cells' attempt to overcome the energy defect through glutaminolysis, a pathway used in particular by cancer cells to support their energy requirements. Moreover, hyper-activation of mTOR inhibits autophagy and these data fit with its reduction in FA, 30 even though in SDS and DBA, autophagy increases. 15 Finally, Ca 2C is a crucial signaling molecule in energy metabolism that regulates many cellular ATP-consuming reactions.…”
mentioning
confidence: 51%
“…17,28,29 In DBA, hyper-activation of mTOR is congruent with the increment in OXPHOS over glycolytic metabolism, while in FA and SDS, hyper-activation of mTOR might suggest the cells' attempt to overcome the energy defect through glutaminolysis, a pathway used in particular by cancer cells to support their energy requirements. Moreover, hyper-activation of mTOR inhibits autophagy and these data fit with its reduction in FA, 30 even though in SDS and DBA, autophagy increases. 15 Finally, Ca 2C is a crucial signaling molecule in energy metabolism that regulates many cellular ATP-consuming reactions.…”
mentioning
confidence: 51%
“…SIN is a single‐stranded RNA virus in the alphavirus family, and numerous previous studies have shown that SIN viral nucleocapsids are degraded by selective autophagy 16, 17, 18. In HeLa cells stably expressing GFP‐LC3 (HeLa/GFP‐LC3 cells) and infected with SIN, four siRNA oligos that target PEX13 (and decrease PEX13 expression [Fig 1A]) resulted in a decrease in colocalization between mCherry‐capsid and GFP‐LC3 puncta (Fig 1B and C).…”
Section: Resultsmentioning
confidence: 99%
“…Like MEFs, primary human fibroblasts do not express endogenous Parkin and CCCP or OA treatment results in Parkin‐independent partial mitochondrial clearance and compaction around the perinuclear region 18. Similar to our findings in CCCP‐treated Pex13 − / − vs. Pex13 + / + MEFs, OA treatment resulted in partial mitochondrial clearance and compaction of remaining mitochondria in the perinuclear region, whereas fragments of damaged mitochondria accumulated throughout the cytoplasm in a higher percentage of PEX13 W313G mutant than PEX13 wild‐type cells (Fig 3E and F).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, novel functions of BRCA2 have been reported and could influence our model of its role in genome stability. Although BRCA2 functions have so far taken place in the nucleus, a recent study raises the intriguing possibility that BRCA2, along with BRCA1 and multiple proteins of the FA pathway (FANCA, FANCF, FANCL, FANCD2), facilitates mitophagy, a cytoplasmic process that targets damaged mitochondria to selective autophagy (Sumpter et al 2016). Mitophagy is critical to maintain low level of mitochondrial reactive oxygen species (mtROS), and recent evidence suggests that the accumulation of mtROS impacts transformation and tumors progression (Chourasia et al 2015).…”
Section: Discussionmentioning
confidence: 99%